Oracles, curses, and risk among the ancient Greeks - Eidinow, Esther, 1970- (Oxford University Press, 2007)
In this book, question tablets from the oracle at Dodona are set side-by-side with curse tablets (katadesmoi or defixiones) from across the Ancient Greek world (for the period 6th-1st centuries BCE). It explores what these texts reveal about perceptions of and responses to the uncertain future, and the nature of risk among ordinary Greek men and women, as well as the insights they afford into civic institutions and activities, and social dynamics. The author follows the anthropologist Mary Douglas in defining ‘risk’ as socially constructed, in contrast to other ancient historians, who treat risk-management as a way of handling objective external dangers. The use of this theory encourages a new approach to both oracles and curses, and in particular, challenges the categories and theories usually used to describe and explain curses. The book includes a full catalogue of all published texts from Dodona, as well as a number of new tablets not published elsewhere, along with the 159 curse tablets discussed, together with translations of all texts.